Perioperative Outcomes Following Surgery of Brain Tumors: Assessment and Analysis of Risk Factors - Kafle, Prakash; Rufus, Phelix; Paudyal, Nabin; Joshi, Narendra P; Khanal, Babita; Jonathan, Gandham E; Chaudhary, Pramod; Bhandari, Binod R; Sharma, Mohan R (Journal of Institute of Medicine Nepal, 2023)
Introduction: Cranial neurosurgery carries significant morbidity and mortality. Hence it is imperative to combine the latest available technological equipment with surgeon’s experience to prevent or reduce perioperative complications. It is also equally important to have a preoperative general assessment of the patient with functional status in particular to predict postoperative outcomes. Methods: This is a prospective study consisting of 122 patients selected over a period of 5 years (March 2017-March 2022). The patient database was retrieved from the medical record department, Nobel Institute of Neurosciences, Nobel Medical College Teaching Hospital, Biratnagar, Nepal and the approval of Institutional review committee was obtained. Age, gender, tumor related factors (site, extent and size), preoperative GCS score, KPS score and mRS grade and their correlation with patient’s perioperative outcome were assessed. Results: Significant correlation was found between preoperative KPS score, mRS grade and patient’s perioperative outcome (low KPS score <70 and high mRS grade was associated with adverse outcomes). There was no positive correlation between age, gender and tumor related factors with outcomes. Conclusion: Low KPS score <70 and a high Modified Rankin scale score were associated with adverse perioperative outcomes in patient’s undergoing elective craniotomy for brain tumor surgery.